Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Fluoride removal by MgO-based adsorbents synthesized via distinct routes: Comparative evaluation of adsorption efficiency and column-scale stability - Yee-Rui Chan; Wei-Han Lin; Wei-Zhe Lin; Rao Y. Surampalli; Ying-Liang Yu; Chih-Ming Kao (Journal of Water Process Engineering, 2025)

Exploring the influence of PCB exposure on neonatal birth outcomes and neurobehavioral development after 15 years of prohibition - Tzu-Hsuen Yuan; Chun-Ju Tai; Cheng-Hsien Tsai; Jien-Wen Chien; Akifumi Eguchi; Chih-Yun Li; Ching-Wen Lin; Chisato Mori; Chang-Chuan Chan (Environmental Pollution, 2025)

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

Quantifying the effects of the microphysical hygroscopic restructuring of soot on ensemble optical properties and satellite aerosol optical depth retrievals - Kuo-En Chang; Tang-Huang Lin; Ta-Chih Hsiao; Yi-Ling Chang; Tzu-Chi Lin; Chih-Yu Chan; Charles C.-K. Chou (Science of The Total Environment, 2024)

Natural shading is helpful but not sufficient for mitigating warming in green sea turtle nests in the tropical South China Sea - Tsung-Han Liu; Ming-Shiou Jeng; Chan-Yuan David Lee; Chih-Wei Tu; Po-Hsiung Lin; Chaolun Allen Chen; Chia-Ying Ko (Biological Conservation, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Environment-friendly organic coordination design of Z-scheme heterojunction N-BOB/BiOIO3 for efficient LED-light-driven photocatalytic and electrochemical performance - Yi-Lun Chen; Li Chen; Ming-Yen Sung; Jung-Hua Lin; Chao-Jan Liu; Chih-Jou Kuo; Er-Chieh Cho; Kuen-Chan Lee (Chemosphere, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Feasibility of a TDR-based technique for fluid hydrocarbon leak detection - Chih-Ping Lin; Yin Jeh Ngui; Yi-Pei Chan; Albert T. Yeung (Process Safety and Environmental Protection, 2023)

HAI-1 is required for the novel role of FGFBP1 in maintenance of cell morphology and F-actin rearrangement in human keratinocytes - Dajun D. Lu; Nanxi Huang; Sheng-Wen A. Li; Jessica R. Fang; Chih-Hsin Lai; Jehng-Kang Wang; Khee-Siang Chan; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2023)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

A First Insight Into the Heat-Induced Changes in Proteomic Profiles of the Coral Symbiotic Bacterium Endozoicomonas montiporae - Ya-Fan Chan; Chia-Yu Chen; Chih-Ying Lu; Yung-Chi Tu; Kshitij Tandon; Shinya Shikina; Sen-Lin Tang (Frontiers in Marine Science, 2022)
Endozoicomonas , a core bacterial group in corals, may also be a coral symbiont. Endozoicomonas communities often decrease rapidly in corals under heat stress. However, how the bacteria respond to changes in temperature and coral host during heat stress is unknown. Here, we employed the cultivable, dominant species E. montiporae as a working organism to explore how Endozoicomonas responds to heat stress. We designed two experiments to clarify the extent to which E. montiporae is influenced by temperature and coral host. We detected differentially expressed protein (DEP) profiles in this bacterium at 31 and 33°C compared to 25°C by tandem mass tags-based quantitative proteome analysis. Fifty DEPs, including many heat shock proteins, were detected when the temperature changed. The expression of antioxidant defense proteins and key pyruvate synthase proteins decreased, suggesting that E. montiporae were in a physiology of stress at 33°C. Furthermore, some proteins were differentially expressed because of the heat-stress-treated coral lysate specifically, suggesting that not only heat but also heat-induced host factors can affect the protein expression of the bacterium. This study provides an in-depth analysis of how the molecular mechanisms of Endozoicomonas are affected by heat stress and coral host.

Global transcriptome analysis and identification of a CONSTANS-like gene family in the orchid Erycina pusilla - Ming-Lun Chou; Ming-Che Shih; Ming-Tsair Chan; Shih-Yi Liao; Chen-Tran Hsu; Yao-Ting Haung; Jeremy J. W. Chen; Der-Chih Liao; Fu-Hui Wu; Choun-Sea Lin (Planta, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

The Effect of Osteochondral Regeneration Using Polymer Constructs and Continuous Passive Motion Therapy in the Lower Weight-Bearing Zone of Femoral Trocheal Groove in Rabbits - Nai-Jen Chang; Chih-Chan Lin; Chien-Feng Li; Kai Su; Ming-Long Yeh (Annals of Biomedical Engineering, 2013)

Novel ionic liquid supported-multicomponent reaction toward chimeric bis-heterocycles - Chih-Hau Chen; Chan-Yu Chen; Po-Tsung Lin; Chung-Ming Sun (Molecular Diversity, 2012)

Ectopic expression of an EAR motif deletion mutant of SlERF3 enhances tolerance to salt stress and Ralstonia solanacearum in tomato - I-Chun Pan; Chia-Wen Li; Ruey-Chih Su; Chiu-Ping Cheng; Choun-Sea Lin; Ming-Tsair Chan (Planta, 2010)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Thiopurine S-methyltransferase activity in three major Asian populations: a population-based study in Singapore - Shirley Kow Yin Kham; Chin Kok Soh; Te Chih Liu; Yiong Huak Chan; Hany Ariffin; Poh Lin Tan; Allen Eng Juh Yeoh (European Journal of Clinical Pharmacology, 2008)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)